The effect of an educational program based on the strategy of generating ideas (Scamper) in the teaching of history on developing critical thinking skills among gifted students in the center of Erbil Governorate. (Raparin Journal of Humanities (RJH), 2024)
The research aims to identify the impact of an educational program based on the strategy of generating ideas (Scamper) in developing critical thinking skills among gifted students. The experimental approach and the two equal groups with pretest and posttest design have been adopted which requires the two groups, one experimental group and the other control group, and two zero hypotheses were formulated to achieve the research objectives. The research community consisted of students of the seventh grade of day schools in the center of Erbil Governorate for the academic year (2021-2022), where (Shinirwe Mixed Basic Education School for the Gifted Students) was chosen, and two classes were chosen randomly from four classes in the seventh grade to be: (a) The Experimental Group and (b) The Control Group, where it included (40) students, of whom (20) twenty students were distributed to the experimental group and (20) other twenty students were distributed to the control group. The experimental group studied according to the educational program based on the strategy of generating ideas (Scamper), while the control group studied according to the traditional (usual) method. To achieve the objectives of the research, the critical thinking standard of (Watson and Kleiser) was used where the number of its paragraphs in its final form has reached to (147) paragraphs distributed on critical thinking skills (hypothesis skill, interpretation skill, discussion skill, reasoning skill, conclusion skill). This is after verifying the validity and reliability using the Cronbach's alpha coefficient, where the reliability coefficient was (0.87) and the reliability coefficient by the two-half method, and after its modification, the value of the stability coefficient was (0.85). Among the most important results reached are the following:There is a statistically significant difference at the level of significance (a = 0.05) between the average grades of the experimental group and the control group in developing critical thinking skills, in favor of the experimental group.In light of the results reached, the two researchers recommended the necessity of adopting an educational program based on the (Scamper) strategy in teaching history, and a number of proposals were proposed.